2010
DOI: 10.1371/journal.pone.0010274
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sponsorship and Failure Rate of Dental Implants: A Systematic Approach

Abstract: BackgroundThe number of dental implant treatments increases annually. Dental implants are manufactured by competing companies. Systematic reviews and meta-analysis have shown a clear association between pharmaceutical industry funding of clinical trials and pro-industry results. So far, the impact of industry sponsorship on the outcomes and conclusions of dental implant clinical trials has never been explored. The aim of the present study was to examine financial sponsorship of dental implant trials, and to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 29 publications
2
48
1
Order By: Relevance
“…This was expected because it has been proved in the literature that smoking affects the healing of bone and mucosa, thus affecting the success rate of implants placed in native alveolar bone and augmented bone. 1,2,5 This negative association was not seen in the autograft and allograft groups, probably because the number of smokers was smaller in these 2 groups compared with the native alveolar bone group.…”
Section: Smokingmentioning
confidence: 92%
“…This was expected because it has been proved in the literature that smoking affects the healing of bone and mucosa, thus affecting the success rate of implants placed in native alveolar bone and augmented bone. 1,2,5 This negative association was not seen in the autograft and allograft groups, probably because the number of smokers was smaller in these 2 groups compared with the native alveolar bone group.…”
Section: Smokingmentioning
confidence: 92%
“…There is some evidence of underreporting of the type, frequency, and severity of adverse effects, such as chipping fracture, bulk fracture, and surface degradation of ceramics, which have been reported in studies that have been supported by corporate sponsors. [11]…”
Section: Limitations Of Clinical Studies Of Ceramic-base Prosthesesmentioning
confidence: 99%
“…[11] concluded that, when controlling for other factors, the probability of annual implant failure for industry-supported trials was significantly lower compared with non-industry-supported trials, and this effect may have adverse implications on decisions regarding tooth extraction, research on tooth preservation, and governmental health care policies. In 41 analyzable trials.…”
Section: Decision Points For Success or Failure?mentioning
confidence: 99%
“…6,[12][13][14][15][16][17][18] For example, annual dental implant failure rates reported in industry-associated trials are significantly lower than those reported in trials without industry support. 19 Dental practitioners' underestimation of the impact of sponsorship bias may influence clinical decision making. In addition, industry sponsorship may influence the ways in which clinical trials are planned, conducted, and reported.…”
Section: Discussionmentioning
confidence: 99%